2015
DOI: 10.1136/bjophthalmol-2015-307167
|View full text |Cite
|
Sign up to set email alerts
|

CADS grading scale: towards better grading of ophthalmic involvement in facial nerve paralysis

Abstract: We present a validation study of an FNGI specifically designed for ophthalmic involvement of FNP. Objective and subjective parameters helped standardise grading and management planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 24 publications
(18 reference statements)
0
19
0
Order By: Relevance
“…Data collection included patient demographics, preoperative and postoperative clinical measurements such as lagophthalmos measurements, and details of revision surgery or adverse event(s), if any. CADS grading scale was recently introduced to better classify the periorbital involvement in patients with facial nerve palsy: corneal involvement, resting or static asymmetry in the periorbital region, dynamic function of periorbital muscles and synkinesis 20. The D-scores in the CADS grading scale are as follows: D 0 =no blink lagophthalmos; D 1 =lagophthalmos on blink <5 mm; D 2 =lagophthalmos on blink ≥5 mm and/or lagophthalmos on gentle closure ≤5 mm; D 3 =lagophthalmos on gentle closure >5 mm and/or lagophthalmos on forced closure >2 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Data collection included patient demographics, preoperative and postoperative clinical measurements such as lagophthalmos measurements, and details of revision surgery or adverse event(s), if any. CADS grading scale was recently introduced to better classify the periorbital involvement in patients with facial nerve palsy: corneal involvement, resting or static asymmetry in the periorbital region, dynamic function of periorbital muscles and synkinesis 20. The D-scores in the CADS grading scale are as follows: D 0 =no blink lagophthalmos; D 1 =lagophthalmos on blink <5 mm; D 2 =lagophthalmos on blink ≥5 mm and/or lagophthalmos on gentle closure ≤5 mm; D 3 =lagophthalmos on gentle closure >5 mm and/or lagophthalmos on forced closure >2 mm.…”
Section: Methodsmentioning
confidence: 99%
“…However, ophthalmologic assessment in this system is limited to whether there is a complete or incomplete eyelid closure and thus, provides an inaccurate picture of eye involvement. The CADS scale [12], combined with standard dry eye evaluation tests, can measure the eye sequelae more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…before surgical correction. The severity of facial nerve palsy was assessed according to the CADS (cornea, static asymmetry, dynamic function, and synkinesis) grading scale reported by Malhotra et al [12]. As corneal staining was evaluated using another grading system described later, the cornea (C) grading system was not used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…In our patients, however, the subgroup analysis comparing patients with and without additional lateral tarsorrhaphy showed almost identical reduction of lagophthalmos, MRD-1, and corneal staining scores. Finally, we have reported the severity of facial palsy using House–Brackmann score, 5 while the use of another classification system named CADS (Cornea, Asymmetry, Dynamic function, Synkinesis) grading, 12 which is more specific for periorbital involvement, could have better encompassed the ophthalmic sequelae of facial palsy. In conclusion, this study showed recession of levator aponeurosis to be an appropriate procedure for addressing paralytic lagophthalmos and exposure keratopathy.…”
Section: Discussionmentioning
confidence: 99%